Research on self-supervised super resolution restoration algorithm based on reflective micro-scanning optical system - Jian Chen; Yuwei Wang; Xin Ye; Mo Chen; Qun Zhou (Scientific Reports)
Abstract The features of infrared image such as less details and low SNR become bottleneck of infrared image application. This paper mainly focuses on research of super-resolution restoration algorithm of infrared image based on reflective infrared micro-scanning optical system. Aiming at solving super-resolution restoration problem of infrared image, self-supervised super resolution restoration algorithm is proposed and optimized. Meanwhile, reflective infrared micro-scanning optical system is introduced to break theoretical limit of simple image processing algorithm. And performance of infrared image super-resolution restoration is improved.